2010
DOI: 10.1155/2010/485306
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone Depletion by Castration May Protect Mice from Heat-Induced Multiple Organ Damage and Lethality

Abstract: When the vehicle-treated, sham-operated mice underwent heat stress, the fraction survival and core temperature at +4 h of body heating were found to be 5 of 15 and 34.4°C ± 0.3°C, respectively. Castration 2 weeks before the start of heat stress decreased the plasma levels of testosterone almost to zero, protected the mice from heat-induced death (fraction survival, 13/15) and reduced the hypothermia (core temperature, 37.3°C). The beneficial effects of castration in ameliorating lethality and hypothermia can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 24 publications
1
7
1
Order By: Relevance
“…At 4 h after WBH, serum levels of IL-6, TNF-a, IL-1b, and nitrite were significantly higher in the heatstroke group than in the sham group [13,14,[22][23][24]. The present study further showed that hypothalamic levels of IL-6, TNF-a, IL-1b, nitrite, and MPO all were upregulated by heatstroke, which could be attenuated by rfVIIa therapy.…”
Section: Discussionsupporting
confidence: 62%
“…At 4 h after WBH, serum levels of IL-6, TNF-a, IL-1b, and nitrite were significantly higher in the heatstroke group than in the sham group [13,14,[22][23][24]. The present study further showed that hypothalamic levels of IL-6, TNF-a, IL-1b, nitrite, and MPO all were upregulated by heatstroke, which could be attenuated by rfVIIa therapy.…”
Section: Discussionsupporting
confidence: 62%
“…Since the presence or absence of tumor cells in TSGs was evaluated one month after castration, we can’t rule out the possibility that the regressed tumors might relapse at later time points. In addition, most studies show a lower serum testosterone level in castrated mice than in humans [26,45-47], possibly because unlike in humans, adrenal glands in mice do not produce androgen [48-50]. Thus, castration of mice may more effectively eliminate HRPCa cells in TSGs than does ADT in humans.…”
Section: Discussionmentioning
confidence: 99%
“…1,13,29 Cast and sham surgery male mice were not tested until a minimum of 14 days after surgery to ensure that all circulating testosterone had diminished. 8,36,65 Experiment 6: Pharmacological Antagonism of N 2 -AcPLZ-Mediated Antinociception in Male Mice Different pharmacological agents were used to determine if the analgesic effects of N 2 -AcPLZ in male mice could be reversed. All antagonists used have previously been shown to not alter formalin behavior compared with VEH treatment alone.…”
Section: Experiments 4 and 5: Effect Of Gonadectomy On Mice Pretreatementioning
confidence: 99%